Perbedaan sikap terhadap proses pelaksanaan otonomi daerah ditinjau dari tipe kepemimpinan dan budaya organisasi - Hadi Suyono (Universitas Ahmad Dahlan, 2004)
The objective this research is to see the different attitude toward the implementation process of the area.autonomy in organization culture at the transformational and transactional leadership types. The subject of the research 124 civil servants of Bantul Regency. The measurement which is used are attitude scale toward the implementation process of the area autonomy, leadership scale types scale, and organization culture scale all of the hypothesis which is presented here are analyzed by the proven anava technique.